Ordering and pricing model of retailers' preventive transshipment dominated by manufacturer with conditional return. (October 2016) - Dan, Bin; He, Qingren; Zheng, Kaiwei; Liu, Ru
Highlights: We develop a model of retailers' preventive transshipment with conditional return. The preventive transshipment policy is a dominant strategy. The existence and uniqueness of ordering Nash equilibrium is proved. The return rate weakens the pricing power of the manufacturer. The transshipment price and wholesale price act as a tool to adjust the ordering quantity of the retailer. Abstract: Retailers often fail to implement the transshipment policy due to lack of the trust or information asymmetry among them in the process of transshipment, especially in the case that return becomes a norm. Therefore, we develop a framework about the preventive transshipment which is dominated by the manufacturer between two independent retailers to cope with the mismatch between demand and inventory. In this research, a two-period ordering and pricing model about the preventive transshipment with conditional return is formulated. To simplify the implementation of preventive transshipment, a dominant preventive transshipment policy is recommended at the beginning of the second period. So, one retailer may adjust the inventory without considering the impact of the other retailer's inventory quantity and the transshipment strategy. To analyze the mutual effect between two retailers, the existence and uniqueness of the ordering Nash Equilibrium and the optimal pricing policy is identified and analyzed. Furthermore, we obtain the relationship between the ordering quantity and transshipment price. Finally, a numerical analysis is carried out to examine the sensitivity of the transshipment price, wholesale price, ordering quantity, profit of the retailer and manufacture to the return rate.